Epidemiology of a sexually transmittable herpesvirus, the Mustelid gammaherpesvirus 1 (MusGHV-1), and its link to reproductive health and physiological stress in European badgers (Meles meles) - Tsai, MS (2021)
Along with virulence and transmissibility, pathogen transmission mode can be decisive on host-pathogen dynamics, where sexually transmitted infections (STIs) are predicted to be more likely to drive vulnerable host population to extinction than infections transmitted mainly through other routes. Despite STIs being common among animals, and often associated with sterility, STIs have been poorly studied in wild animals. As a background introduction to the current state of knowledge about wildlife STIs, in Chapter 1 I reviewed studies reporting STIs in wild musteloids; a group substantially ignored in previous STI reviews. The high proportion of reported cases associated with reproductive diseases and failure, and disproportionally investigation effort in wild populations highlight the need for further research, especially in species of conservation concern. I established the need for systematic wild mammal host-STI models to better understand the actual impact of STIs on wildlife health and population dynamics. In Chapter 2, I laid the foundations for investigating a sexually transmittable pathogen, the Mustelid gammaherpesvirus 1 (MusGHV-1), in free-ranging European badgers (Meles meles), and reported that MusGHV-1 reactivation has a negative effect on female pregnancy success, but not on male sperm abundance. In Chapter 3, I explored influential host risk factors associated with higher MusGHV-1 shedding, such as age, body conditions and sex. In Chapter 4, I explored the effect of MusGHV-1 coinfection with a zoonotic bacterial pathogen, Clostridium perfringens. MusGHV-1 reactivation causes a predisposition to C. perfringens overgrowth in the gut, especially when infected with a novel MusGHV-1 variant. This led me to further explore the genetic and phenotypic differences between the two MusGHV-1 variants identified in this badger population in Chapter 5. I found social group-biased MusGHV-1 variant frequencies and blood viral load differences, implying different functional virulence between the two variants. In Chapter 6, I identified that weather-related stress experienced during prenatal life exacerbate the likelihood of MusGHV-1 reactivation in adulthood. Collectively, these chapters reveal the potential for host responses to viral STI’s to be complex, hinging on individual demographics, coinfection status, environmental conditions, and the viral strain involved; all factors needing proper consideration when attempting to mitigate the role of disease in conservation ecology.